Circularly Polarized Triband Printed Quasi-Yagi Antenna for Millimeter-Wave Applications - Dalia M. Elsheakh; Magdy F. Iskander (International Journal of Antennas and Propagation)
This paper describes the design and development of a triband with circularly polarized quasi-Yagi antenna for ka-band and short range wireless communications applications. The proposed antenna consists of an integrated balun-fed printed dipole, parasitic folded dipole and a short strip, and a modified ground plane. The antenna structure, together with the parasitic elements, is designed to achieve circular polarization and triband operating at resonant frequencies of 13.5 GHz, 30 GHz, and 60 GHz. Antenna design was first simulated using HFSS ver.14, and the obtained results were compared with experimental measurements on a prototype developed on a single printed circuit board. Achieved characteristics include −10 dB impedance bandwidth at the desired bands, circular polarization axial ratio AR<3 dB, front to back ratio of 6 dB, gain value of about 4 dBi, and average radiation efficiency of 60%. The paper includes comparison between simulation and experimental results.